Poverty knowledge : social science, social policy, and the poor in twentieth-century U.S. history - O'Connor, Alice, 1958- (Princeton, N.J. : Princeton University Press, 2001)
Progressive-era "poverty warriors" cast poverty in America as a problem of unemployment, low wages, labor exploitation, and political disfranchisement. In the 1990s, policy specialists made "dependency" the issue and crafted incentives to get people off welfare. Poverty Knowledge gives the first comprehensive historical account of the thinking behind these very different views of "the poverty problem," in a century-spanning inquiry into the politics, institutions, ideologies, and social science that shaped poverty research and policy. Alice O'Connor chronicles a transformation in the study of poverty, from a reform-minded inquiry into the political economy of industrial capitalism to a detached, highly technical analysis of the demographic and behavioral characteristics of the poor. Along the way, she uncovers the origins of several controversial concepts, including the "culture of poverty" and the "underclass." She shows how such notions emerged not only from trends within the social sciences, but from the central preoccupations of twentieth-century American liberalism: economic growth, the Cold War against communism, the changing fortunes of the welfare state, and the enduring racial divide
Origins: poverty and social science in the era of progressive reform -- Poverty knowledge as cultural critique: the Great Depression -- From the Deep South to the dark ghetto: poverty knowledge, racial liberalism, and cultural "pathology" -- Giving birth to a "culture of poverty": poverty knowledge in postwar behavioral science, culture, and ideology -- Community action -- In the midst of plenty: the political economy of poverty in the affluent society -- Fighting poverty with knowledge: the Office of Economic Opportunity and the analytic revolution in government -- Poverty's culture wars -- The poverty research industry -- Dependency, the "underclass," and a new welfare "consensus": poverty knowledge for a post-liberal, postindustrial era -- The end of welfare and the case for a new poverty knowledge.
Includes bibliographical references and index.
Print version record.
English.
JSTOR
Keywords: Umschulungswerkstätten für Siedler und Auswanderer; Poverty -- United States -- History -- 20th century; Poor -- United States -- History -- 20th century; Economic assistance, Domestic -- United States -- History -- 20th century; Unemployment; Welfare recipients; Unemployment; Class consciousness; Pauvreté -- États-Unis -- Histoire -- 20e siècle.; Pauvres -- États-Unis -- Histoire -- 20e siècle.; Aide au développement économique régional -- États-Unis -- Histoire -- 20e siècle.; Chômage.; unemployment; SOCIAL SCIENCE -- Poverty & Homelessness; Unemployment; Economic assistance, Domestic; Poor; Poverty; United States; Armut; Sozialhilfe; Sozialpolitik; Sozialwissenschaften; USA; Sociaal-wetenschappelijk onderzoek; Armoede; Sociale politiek; Pauvreté -- Etats-Unis -- 20e siècle.; Pauvres -- Etats-Unis -- 20e siècle.; USA; 1900-1999; History